Penyuluhan CERDIK Dan Deteksi Dini Hipertensi Melalui Cek Tekanan Darah Gratis Bagi Lansia Di Posyandu Lansia Kelurahan Antang Makassar - Muh. Asrul Taufiq Arifuddin (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
ABSTRACT Hypertension is one of the most common degenerative diseases among the elderly and remains a major public health problem due to its association with cardiovascular disease, stroke, and kidney failure. Elderly individuals often experience uncontrolled blood pressure because of limited knowledge regarding healthy lifestyles and inadequate routine health monitoring. The CERDIK program promoted by the Ministry of Health serves as a preventive approach to reduce hypertension risk factors through healthy behavior. This community service activity aimed to improve elderly knowledge regarding hypertension prevention through CERDIK education and early detection by providing free blood pressure examinations. The activity was conducted at the Elderly Posyandu in Antang Village, Makassar, involving 45 elderly participants. Methods included health education, interactive discussions, blood pressure screening, and evaluation using pre-test and post-test questionnaires. The results demonstrated an increase in the average knowledge score from 59.6 before education to 86.8 after the intervention. Blood pressure examination revealed that 24 participants (53.3%) had hypertension, while 15 participants (33.3%) were classified as prehypertensive. The program successfully improved participants’ knowledge and awareness regarding hypertension prevention and the importance of regular blood pressure monitoring.